2014
DOI: 10.1091/mbc.e13-08-0434
|View full text |Cite
|
Sign up to set email alerts
|

The ShcD signaling adaptor facilitates ligand-independent phosphorylation of the EGF receptor

Abstract: Shc proteins traditionally couple ligand-activated receptor tyrosine kinases to proximal effectors in signal transduction cascades. ShcD challenges this paradigm by activating the EGF receptor from within the cell, circumventing the need for extracellular stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 52 publications
8
35
0
Order By: Relevance
“…Our findings further underscore the non-canonical characteristics of ShcD, which may be of particular relevance to the malignancies in which ShcD is overexpressed, including glioma (Wills et al, 2014) and melanoma (Fagiani et al, 2007).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our findings further underscore the non-canonical characteristics of ShcD, which may be of particular relevance to the malignancies in which ShcD is overexpressed, including glioma (Wills et al, 2014) and melanoma (Fagiani et al, 2007).…”
Section: Introductionsupporting
confidence: 60%
“…Intriguingly, the AP2 adaptin-binding motif (AD) is conserved across all Shc adaptors except ShcD, and the physiological consequence of this loss has not yet been investigated. We have previously shown that ShcD is an EGFR binding partner that possesses the unique capacity to promote ligand-independent phosphorylation of the receptor on three physiologically relevant sites -Y1068, Y1148 and Y1173 (Wills et al, 2014). This phenomenon was found to require both the intrinsic EGFR kinase, and the PTB domain of ShcD.…”
Section: Introductionmentioning
confidence: 98%
“…3). Of note, MIA, S100B, FABP7, and SHC4/RaLP have been previously linked to melanoma 6568 and glioma 6971 . Overall, we identified 10 basic cell lineage markers shared between ACC, BBC, melanoma, and Schwann cells that strongly supported our hypothesis on the origin of these three cancers from Schwann cell precursors (FIG.…”
Section: Resultsmentioning
confidence: 93%
“…Sch4 is maximally expressed at stages IIÀIII, and the docking protein is concentrated at the plasma membrane, where it facilitates ligand-independent phosphorylation of the epidermal growth factor (EGF) receptor, which is also expressed by Sertoli cells [69,70]. This phosphorylation allows for cross talk between different receptor systems, leading us to suggest that the stage-dependent increase in SCH4 allows the efficient integration of multiple signaling pathways in Sertoli cells [71].…”
Section: A Kinase Anchoring Proteinsmentioning
confidence: 99%
“…Maximal expression of these genes occurs at stages VIIc,d, VIII, and IXÀXI, respectively. Maff is noteworthy because its protein product suppresses EGF-driven gene transcription and because its stage-specific pattern of expression is the opposite of that of Sch4, which facilitates ligand-independent phosphorylation and activation of the EGF -receptor [69]. Two transcriptional repressors complete this list: HOP homeobox (Hopx) and zinc finger homeobox 3 (Zfhx3), which are maximally expressed at stages 298 Sertoli Cell Biology VI and VIIc,d, respectively.…”
Section: Transcriptional Activators and Repressorsmentioning
confidence: 99%